The Semantic Significance of Frege’s Puzzle - Greimann, Dirk (2015)
In “Can Frege Pose Frege’s Puzzle?”, Stavroula Glezakos argues that Frege’s puzzle about the cognitive significance of identity statements does not have the status of a genuine problem of semantics. The puzzle arises only on the condition that Frege’s specific solution of the puzzle is accepted. From this she concludes that Frege cannot really pose his puzzle. Neither Non-Fregeans nor Fregeans should be puzzled by it. The aim of this paper is to show that Glezakos’ deflationary assessment of the puzzle cannot be sustained. It is argued that Frege’s puzzle does not refer to the semantic analysis of natural language, as Glezakos and also Howard Wettstein assume, but to the construction of a semantic interpretation for the language of science that allows us to communicate our cognitive acts and attitudes in an adequate way. So understood, the puzzle has the status of a genuine problem whose solution is a key problem of semantics.